Obtention of a Sensitive Acylated Pyrogallol[4]arene-Based Sensor for the Detection of Carnitine: A Spectroscopic and DRX Study - José Luis Casas-Hinestroza; Adrián Pérez-Redondo; Mauricio Maldonado (Analytica)
Complexation between carnitine and acetylated or benzylated pyrogallol[4]arenes was studied in DMSO via dynamic NMR, UV-vis spectroscopy, and in the gas phase via electrospray ionization-mass spectrometry (ESI-MS). In the presence of benzylated tetra(phenyl)pyrogallol[4]arene, the interaction with carnitine via NMR was evident and was confirmed by means of UV-vis spectroscopy, where the formation of a host–guest-type complex was observed; this was stable and exhibited a change to a clear color. With benzylated tetra(propyl)pyrogallol[4]arene, the results showed that there was no interaction with the neurotransmitter. A plausible explanation for this behavior is based on the dynamic behavior of the benzylated tetra(propyl)pyrogallol[4]arene, and this shows the dependence on the size of the cavities and the substituent on the lower rim of the pyrogallo[4]arenes. Suitable crystals of O-acetylated-tetra(propyl)calix[4]pyrogallolarene were obtained and were characterized through an X-ray crystal structure determination.